2017
DOI: 10.14814/phy2.13054
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial efficiency and exercise economy following heat stress: a potential role of uncoupling protein 3

Abstract: Heat stress has been reported to reduce uncoupling proteins (UCP) expression, which in turn should improve mitochondrial efficiency. Such an improvement in efficiency may translate to the systemic level as greater exercise economy. However, neither the heat‐induced improvement in mitochondrial efficiency (due to decrease in UCP), nor its potential to improve economy has been studied. Determine: (i) if heat stress in vitro lowers UCP3 thereby improving mitochondrial efficiency in C2C12 myocytes; (ii) whether he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
2
9
2
Order By: Relevance
“…Contrary to our hypothesis, markers of oxidative phosphorylation did not increase in response to HA. These results are contrary to previously mentioned cell (Liu & Brooks, 2012;Salgado et al, 2017) and rodent (Tamura et al, 2014) models as well as some recent human studies (Hafen et al, 2019;Hafen, Preece, Sorensen, Hancock, & Hyldahl, 2018 and 50 min per session) showed no changes in mitochondrial density by COX-4 protein expression using microscopy (Hesketh et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our hypothesis, markers of oxidative phosphorylation did not increase in response to HA. These results are contrary to previously mentioned cell (Liu & Brooks, 2012;Salgado et al, 2017) and rodent (Tamura et al, 2014) models as well as some recent human studies (Hafen et al, 2019;Hafen, Preece, Sorensen, Hancock, & Hyldahl, 2018 and 50 min per session) showed no changes in mitochondrial density by COX-4 protein expression using microscopy (Hesketh et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…While the organism‐level adaptations to HA are well‐established, less is known about the cellular response to HA protocols (Sawka, Leon, Montain, & Sonna, 2011). In isolated skeletal muscle cells, repeated heat stress evokes mitochondrial biogenesis and oxidative phenotypic shifts that increase mitochondrial density (Liu & Brooks, 2012; Patton et al., 2018) and efficiency (Salgado et al., 2017). Liu & Brooks (2012) demonstrated that repeated heat stress upregulated several molecules in the PGC1‐α signalling pathway, including nuclear AMP‐activated protein kinase (AMPK), sirtuin 1 (SIRT‐1), nuclear respiratory factors (NRF1 and 2), and oxidative phosphorylation subunits I–III in mouse myoblast.…”
Section: Introductionmentioning
confidence: 99%
“…As these knockout animals were not exposed at high temperature, there is no evidence for a direct involvement of UCP3 in heat acclimation. However, it has been shown that Ucp3 expression was reduced in the hypothalamus of meat-type chicken after heat stress 33 and that heat-stressed C2C12 murine myocytes displayed also a significant reduction of Ucp3 mRNA expression compared to control 34 . UCP3 therefore remains an interesting candidate gene to explain thermo-tolerance in CHCU, despite further work being needed.…”
Section: Resultsmentioning
confidence: 95%
“…Increased ROS production has been reported in several HS animals (Huang et al, 2015;Kikusato et al, 2016;Banh et al, 2016). Reduced expression of avUCP in muscule after acute HS exposition of chickens (Kikusato et al, 2016) and heat acclimation of myocytes (Salgado et al, 2017) has been reported. Mujahid et al (2007) observed that 18 h of heat stress (34°C) stimulated the superoxide production in mitochondria, probably by down-regulation of avUCP in muscle tissue.…”
Section: Discussionmentioning
confidence: 95%